Foundations of information security a straightforward introduction - Andress, Jason (No Starch Press, 2019)
A valuable resource for beginning security professionals, network systems administrators, or anyone new to the field, this book is a great place to start your journey into the dynamic and rewarding field of information security. --
Includes bibliographical references and index. - Online resource; title from title page (Safari, viewed October 24, 2019)
Keywords: Computer security; Computer networks -- Security measures; Electronic information resources -- Access control; Computer Security; Sécurité informatique; Réseaux d'ordinateurs; Sécurité; Mesures; Sources d'information électroniques; Accès; Contrôle; Computer networks; Security measures; Electronic information resources; Access control